Practical statistics for nursing and health care - Fowler, Jim, 1943- (Wiley, 2013)
Nursing is a growing area of higher education, in which an introduction to statistics is an essential component. There is currently a gap in the market for a 'user-friendly' book which is contextulised and targeted for nursing. Practical Statistics for Nursing and Health Care introduces statistical techniques in such a way that readers will easily grasp the fundamentals to enable them to gain the confidence and understanding to perform their own analysis. It also provides sufficient advice in areas such as clinical trials and epidemiology to enable the reader to critically appraise work published in journals such as the Lancet and British Medical Journal.